Economies of signs and space - Lash, Scott; Urry, John. (London ; Thousand Oaks, Calif. : Sage, 1994)
Economies of Signs and Space presents a novel account of social change that supplants conventional understandings of 'society'. In this extraordinary and wide-ranging book, two eminent theorists develop a sociology that takes as its main unit of analysis social and cultural flows through time and across space. Focusing on post-industrial economies, the study examines social inequality and changing experiences of time, space, culture, travel, the environment and globalization. Through a comparative analysis of the UK and USA, Germany and Japan, Lash and Urry show how restructuration after organized capitalism has its basis in increasingly reflexive social actors and organizations. The consequence is not only the much-vaunted 'postmodern condition' but a growth in reflexivity.
In exploring this new reflexive world, Lash and Urry argue that today's economies are increasingly economies of signsinformation, symbols, images, desire - and of space, where both signs and social subjects - refugees, financiers, tourists, flaneurs - are mobile over ever greater distances. They show how an understanding of such flows contributes to the analysis of changes in social relations, from the organization of work to the 'culture industries', from the formation of an underclass to new forms of citizenship. Taking its point of departure from the authors' influential The End of Organized Capitalism, this is a book that no one in social and cultural theory, geography and urban studies, political economy, and organization studies can afford to ignore.
Polarization: poverty and professionals. The politics of space and the making of the underclass. 7. Mobile Subjects: Migration in Comparative Perspective. Migration after organized capitalism. Case-study: clothing and fashion. Corporatist exclusion in a reunited Germany -- part 3. Economies of Space and Time. 8. Post-Industrial Spaces. Restructuring services. Restructuring and the public sector. Services and the restructuring of place. 9. Time and Memory. Sociology of time. Time and the duality of structure. Time, powers and nature. Disorganized capitalism and time -- part 4. Globalization and Modernity. 10. Mobility, Modernity and Place. Travel and modernity. The emergence of organized tourism. Tourist services and disorganized capitalism. 11. Globalization and Localization. Money and finance. Nature and the environment. Global culture and national culture -- 12. Conclusion.
Cover title: Economies of signs and space.
Includes bibliographical references (pages 327-350) and index.
Keywords: Economics -- Sociological aspects; Social change; Social history -- 20th century; Social interaction; Postmodernism -- Social aspects; Space and time; Signs and symbols; Social change